Kajian Ekstrak Daun Kemangi dalam Mempertahankan Kesegaran Ikan Layang (Decapterus sp) - I Gede Wenda Wikan Adi; A.A. Made Semariyani; Nyoman Rudianta; I Wayan Sudiarta; I Putu Candra (Fakultas Pertanian, Universitas Warmadewa, 2020)
Basil leaves are small clumps of shrubs and have long leaves such as spurs that are widely favored by Indonesian people as fresh vegetables and rich in flovanoid compounds, tannins, safonins, and essential oils function as anti-microbial properties. This study aims to determine the characteristics of the flying fish due to the influence of the use of the concentration of basil extract and soaking time and find out how long the basil extract can maintain the freshness of the flying fish. This research was conducted at the Food Analysis Laboratory of the Warmadewa Faculty, Denpasar Veterinary Center, and LPPMHP Denpasar. This research is a factorial experiment with a randomized block design (RBD) consisting of 2 factors: namely factor I, duration of immersion consisting of 2 levels, namely 1 hour and 2 hours soaking. Factor II, storage time which consists of 3 levels: 2 days, 4 days and 6 days. Variables observed in flying fish include objective observations namely analysis of water content, pH value, Total Volatile Base (TVB) value, and Total Plate Count (TPC) value. Whereas subjective observations included tests on the appearance of eyes, appearance of meat, odor / odor, and texture. The best freshness quality of the flying fish is objectively obtained in the 2 hour immersion treatment with 6 days storage time in cold temperatures (10 Â± 5) ËšC and subjectively the effect of each treatment on variables, appearance of meat, odor / odor, and the texture is still good and acceptable. Overall treatment test results compared with Indonesian National Standard No. 2729-2013 shows that the test results variable meets the requirements.